IDENTIFICATION OF B-CELL AND T-CELL SPECIFIC PEPTIDE VACCINE FOR SERRATIA MARCESCENS - Hidhayathul Wajeeha; Sathish Sankar* (Chelonian Research Foundation, 2023)
Introduction: Serratia marcescens is an opportunistic, gram negative, nosocomial pathogen which belongs to family, Enterobacteriaceae. It was discovered by Bizio, an Italian pharmacist, in 1819, when he identified it as a cause of the bloody discolouration on cornmeal mush. He named the organism in honour of the Italian physicist, Serratia who invented the steam boat and marcescens, which is the latin word for ‘decaying’, as the bloody discolouration on cornmeal disappeared quickly. Materials and methods: In silico analyses utilizing bioinformatic tools were employed to screen the genome and proteome of S. marcescens, predicting candidate epitopes with high antigenic and immunogenic potential. The selection criteria included binding affinity to major histocompatibility complexes (MHC) for T-cell activation and surface accessibility for B-cell recognition. Results: The identified B-cell epitope, displaying 100% homology to Serratia marcescens and meeting the optimal length criteria, stands out as a prime contender for integration into the vaccine. Moreover, the top-scoring T-cell epitope adds a vital facet to the vaccine approach, aligning with current epitope prediction trends to bolster the immune response significantly. Conclusion: The peptide sequences identified show great promise, functioning effectively as both B-cell and T-cell epitopes. Their strong affinities for various HLA alleles and robust interactions with MHC molecules suggest their capability to stimulate a powerful immune response across a wide population. These qualities support their suitability for a universal vaccine strategy. Keywords: Serratia marcescens, peptide vaccine, B-cell epitopes, T-cell epitopes, immunoinformatics, antigen prediction, vaccine development, universal health, diseases, Well being, health, international health policy.